To find the solution for both equations, you can set them equal to each other:
-x + 3 = -2x + 6
Add x to both sides:
3 = -x + 6
Subtract 3 from both sides:
-3 = -x
Now, multiply both sides by -1 to solve for x:
3 = x
Therefore, the solution is x = 3. Now, substitute this value back into one of the original equations to solve for y. Let's use y = -x + 3:
y = -(3) + 3
y = -3 + 3
y = 0
Therefore, the solution to the system of equations y = -x + 3 and y = -2x + 6 is x = 3 and y = 0.
what would be the solution of y= -x+3 and y=-2x+6
1 answer